2002
DOI: 10.2170/jjphysiol.52.421
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Blood Pressure and Muscle Sympathetic Nerve Activity during Water Drinking in Humans.

Abstract: Water drinking is recognized to be an essential behavior for fluid homeostasis and is frequently and necessarily observed in daily life. Water drinking causes many physiological changes, including fluctuations in endocrine function, cardiovascular system, and fluid balance during or immediately after drinking [1][2][3][4][5][6][7]. Because these changes occur in the early phase of drinking, the contribution of absorbed water from the gastrointestinal tract may be little, if any, but neural factors such as refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
5
20
0
1
Order By: Relevance
“…2001). This was not reproduced in a later study (Endo et al. , 2002), where a transient pressor response and increase in MSNA occurred only whilst drinking.…”
Section: Cardiovascular Autonomic Responses To Water Ingestionmentioning
confidence: 60%
See 1 more Smart Citation
“…2001). This was not reproduced in a later study (Endo et al. , 2002), where a transient pressor response and increase in MSNA occurred only whilst drinking.…”
Section: Cardiovascular Autonomic Responses To Water Ingestionmentioning
confidence: 60%
“…In one study, muscle sympathetic nerve activity (MSNA) measured by microneurography increased 20 min after ingestion, peaked at 30 min and returned to control levels at 50 min (Scott et al 2001). This was not reproduced in a later study (Endo et al, 2002), where a transient pressor response and increase in MSNA occurred only whilst drinking.…”
Section: Cardiovascular Autonomic Responses To Water Ingestionmentioning
confidence: 65%
“…Oropharyngeal activation, 27 gastric dilatation, 27,28 osmosensitive afferent structures in the gastrointestinal tract 29 and rehydration of subtle volume depletion 30 have all been implicated. Oropharyngeal activation, 27 gastric dilatation, 27,28 osmosensitive afferent structures in the gastrointestinal tract 29 and rehydration of subtle volume depletion 30 have all been implicated.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Water intake has been proposed by our group as an effective strategy to improve HR recovery after moderate intensity exercise 5,6 . However, studies have shown that water intake promotes an increase in BP through sympathetic activation 7 , a response that may inhibit PEH. In this respect, Endo et al 8 investigated the effects of water intake on postexercise BP responses and observed the absence of PEH.…”
Section: Introductionmentioning
confidence: 99%